INFLUENCE OF THE PIEZOELECTRIC CONSTITUTIVE AND MECHANICAL DUFFING-TYPE NONLINEARITIES ON VIBRATION-BASED ENERGY HARVESTING - Cellular, Ana Carolina (2017)
Vibration-based energy harvesting has the main objective to convert available environment mechanical energy into electrical energy. Piezoelectric materials are usually employed to promote the mechanical-electrical conversion. This work investigates the influence of nonlinear effects in piezoelectric vibration-based energy harvesting. Mechanical nonlinearities are treated considering Duffing-type mechanical oscillator. Piezoelectric nonlinearities are analyzed assuming quadratic constitutive coupling model. Energy harvesting performance is evaluated for different system characteristics being monitored by the input and the generated power. Numerical simulations are carried out considering different kinds of responses, including periodic and chaotic regimes.